EFEKTIVITAS MODEL THINK PAIR AND SHARE TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS DAN PEMECAHAN MASALAH PADA MATERI SPLTV SISWA KELAS X SMA NEGERI 1 HABINSARAN T.P. 2023/2024 - Pasaribu, Mei Sartika; Tambunan, Hardi; Sinaga, Samuel Juliardi (Jurnal Curere, 2024)
This study aims to determine the effectiveness of the think, pair, and share model on the ability to think creatively in mathematics and solve problems in the material of three-variable linear equation systems of class X students of SMA Negeri 1 Habinsaran in the academic year 2023/2024. The type of research used is quasi-experimental. The research population was all class X, and the research sample consisted of 72 class X students. The sampling technique was carried out using the Incidental sampling technique. The instruments used were questionnaires and tests. Hypothesis testing in this study used the F test. The results of the study showed that: (1) Learning with the think, pair, and share model is effective in students' ability to think creatively in mathematics. (2) The effectiveness of the think, pair, and share model on students' ability to think creatively in the high category. (3) Learning with the think, pair, and share model is effective in students' ability to solve problems. (4) The effectiveness of the think, pair, and share model on problem-solving abilities in the high category.